Non-Middle east oil Producing Countries: detailed forecasts to 1985 - Morrel, James (The Henley Centre for Forecasting London, 1976)
This examines the economics of the principle oil producers outside the middle east, forecasts their development , both social and economic.
aia 26/02/2019
Loans
Keywords: Oil countries; Middle East